The status and influencing factors of abnormal fetal pregnancy outcomes in 265 cases in China: a retrospective study - Ruan, Jing; Zhong, Xuemei; Mai, Jiaxuan; Liu, Cuifen; Ding, Huiyang (PeerJ, 2024)
Background With the advancement of prenatal diagnosis technology, the detection rate of fetal abnormalities continues to increase, imposing a significant burden on both society and families. A retrospective analysis of essential information about pregnant women, such as their pregnancy history and delivery details, is crucial for understanding the primary factors that influence pregnancy outcomes in women with fetal abnormalities. This analysis is of great significance for improving the level of pregnancy management and outcomes in pregnant women with fetal abnormalities. Objective To retrospectively analyze the pregnancy outcomes of women with fetal abnormalities and explore the factors that influence these outcomes. Methods Pregnant women’s pregnancy outcomes were collected from the medical information system and through telephone follow-ups. The chi-square test and logistic regression were used to analyze the factors influencing pregnancy outcomes. Results Among 265 pregnant women diagnosed with fetal abnormalities, 190 chose to continue the pregnancy, while 75 chose to terminate it. Pregnant women with multiple fetal abnormalities (OR = 3.774, 95% CI [1.640–8.683]) were more likely to choose termination of pregnancy (TOP), and pregnant women who were advised to terminate their pregnancy or make a careful choice were more likely to terminate the pregnancy (OR = 41.113, 95% CI [11.028–153.267]). Conclusion The number of organs involved in fetal abnormalities and treatment recommendations were identified as the primary factors influencing pregnancy outcomes. Improving awareness of maternal health care during pregnancy, early pregnancy screening technology, and a multidisciplinary diagnosis and treatment approach are of great significance in assisting pregnant women in making informed decisions and improving fetal prognosis.
Keywords: Fetal anomaly; Pregnancy outcome; Influence factor; Retrospective analysis